Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar dan Aktivitas Belajar Matematika - Hadi, Muh. Saipul; Junaidi, Junaidi; Maksud, Maksud (FKIP Universitas Mataram, 2025)
AbstractThis study aims to improve the learning outcomes and learning activities of Grade 7F students at SMPN 2 Mataram on the topic of angles through the implementation of the Problem-Based Learning (PBL) model. This research is a Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in three cycles, with each cycle consisting of two meetings. Data were collected through learning outcome tests and student activity questionnaires using a Likert scale. The results showed a significant improvement in students’ learning outcomes, with the percentage of students achieving the minimum mastery criteria increasing from 65% in Cycle I, to 80% in Cycle II, and 90% in Cycle III. The number of students who achieved mastery also increased, from 10 students (23.25%) in Cycle I, to 21 students (48.84%) in Cycle II, and 37 students (86.05%) in Cycle III. Students’ learning activities also improved, with recorded percentages of 55.81% in Cycle I, 74.42% in Cycle II, and 88.37% in Cycle III. Keywords: Problem Based Learning, Learning Outcomes, Learning Activities